2001
DOI: 10.4049/jimmunol.166.1.403
|View full text |Cite
|
Sign up to set email alerts
|

Group 1 CD1 Genes in Rabbit

Abstract: CD1 is an Ag-presenting molecule that can present lipids and glycolipids to T cells. The CD1 genes were first identified in the human, and since then, homologs have been identified in every mammalian species examined to date. Over a decade ago, CD1B and CD1D homologs were identified in the rabbit. We have extended this earlier study by identifying additional CD1 genes with the goal of developing the rabbit as an animal model to study the function of CD1 proteins. We constructed a thymocyte cDNA library and scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…In man, CD1a, CD1b, CD1c, and possibly CD1e are group 1 molecules, and CD1d is a member of the group 2 CD1 molecules. Mice and rats have only group 2 CD1 molecules (Balk et al 1991;Ichimiya et al 1994), but rabbit and sheep have both groups of CD1 molecules (Calabi et al 1989a;Dascher et al 1999;Hayes and Knight 2001), indicating that group 1 CD1 genes were lost in a rodent lineage (Dascher and Brenner 2003). Phylogenetic analysis indicates that chicken CD1.1 and CD1.2 are neither group 1-nor group 2-like and that the duplication event that gave rise to chicken CD1.1 and CD1.2 took place independently from the one that created the two groups of mammalian CD1 genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In man, CD1a, CD1b, CD1c, and possibly CD1e are group 1 molecules, and CD1d is a member of the group 2 CD1 molecules. Mice and rats have only group 2 CD1 molecules (Balk et al 1991;Ichimiya et al 1994), but rabbit and sheep have both groups of CD1 molecules (Calabi et al 1989a;Dascher et al 1999;Hayes and Knight 2001), indicating that group 1 CD1 genes were lost in a rodent lineage (Dascher and Brenner 2003). Phylogenetic analysis indicates that chicken CD1.1 and CD1.2 are neither group 1-nor group 2-like and that the duplication event that gave rise to chicken CD1.1 and CD1.2 took place independently from the one that created the two groups of mammalian CD1 genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD1b in leprosy lesions was confirmed in a study that linked this to the development of increased local immunity to M. leprae, and suggested that toll-like receptor signaling could induce monocytes to differentiate into these group 1 CD1 + dendritic cells [16]. Recent progress in defining group 1 CD1 molecules in a variety of other mammalian species, such as guinea pigs [9,17,18], rabbits [19], cows [20], and nonhuman primates [21], may allow the development of more advanced studies on the modulation of group 1 CD1 molecules by infection in vivo.…”
Section: Expression Of Group 1 Cd1 and Its Modulation By Infectionmentioning
confidence: 81%
“…Genomes from these nine mammalian species contain from one (rat (Katabami et al 1998)) to thirteen (horse and dog (Dossa et al 2014; Schjaerff et al 2016)) CD1 genes. From rabbits, two CD1a, two CD1b, one CD1d, and one CD1e transcripts have been identified, but this study was not set up or intended to define the complete rabbit CD1 locus (Hayes and Knight 2001). Southern blots suggested the presence of at least eight CD1 genes in the rabbit (Calabi et al 1989).…”
Section: Cd1 In Humans and Common Research Farm And Companion Animalsmentioning
confidence: 99%
“…However, only two of the three studied canine CD1a genes (out of the nine CD1a genes in the dog CD1 locus) were preferentially expressed in the skin. In rabbits, one of the two CD1a genes is preferentially expressed in the skin, while the other one has a more general expression pattern (Hayes and Knight 2001). In guinea pigs, different CD1b genes have different expression patterns in peripheral blood and spleen (Hiromatsu et al 2002).…”
Section: Expression Patterns Of Cd1 Isoformsmentioning
confidence: 99%